Biology and Management of Yellow (Cyperus escuelentus) and Purple Nutsedge (C. rotundus) in Ornamental Crop Production and Landscapes - Debalina Saha; Stephen Christopher Marble; Nathan Boyd; Shawn Steed (EDIS)
This new six-page document provides insight on characteristics and management techniques for both yellow and purple nutsedge, prevalent and persistent weeds in Florida. Written by Debalina Saha, Chris Marble, Nathan Boyd, and Shawn Steed and published by the UF/IFAS Environmental Horticulture Department, March 2019. http://edis.ifas.ufl.edu/ep569